Routing selection algorithm based on ant colony optimization in mobile P2P network - Lifang MA; Weifeng CHEN; Shizhan LAN; Song LU; Yulan ZHANG; Xiaobin MO; Changzhi HE (Dianxin kexue)
For the dynamic of P2P network and the limited energy of the mobile node,enhancing the mobile P2P data transmission efficiency is essential.By using ant colony optimization algorithm the ant pheromones were combined with the node energy and communication bandwidth.When ACO selected the path,the concentration of the pheromone on its optimization path was reduced.The routing selection strategy was adaptively adjusted by the pheromone density of routing probability table in order to avoid network congestion and excessive energy consumption of individual nodes.A multipath routing selection algorithm in mobile P2P network was proposed.Experiment results show that the proposed algorithm can reduce packet loss rate and the average delay compared with EDSR routing protocol,prolonging the lifecycle of the whole network.